ETIKA ISLAM DAN EKONOMI KERAKYATAN - Musa Asy'arie (Faculty of Economics and Business, Universitas Gadjah Mada, 1999)
In a new Indonesian format, there appears a great desire to accelerate people's economy as the basis of the economic stability and national defense. This is due to the fact that indicates that the collapse of the Indonesian economy nowadays is dramatically caused by the weakness of the fundamentals of the national economy in which small and mediom enterprises cannot get a chance to develop to a maximum.It is in this effort that the populist's economy as an economic system oriented to people's interest and empowerment may be an alternative to make it awake. This means shifting from a capitalistically economic system to a populist's one. Hence, it is necessary to make an integral, actual and realistic concept which may be implemented in the concrete and consistent policy and conduct of political economy. In addition, the problems faced to carry out the populist' economic system are: 1) culture, 2) structure, 3) environment. The first problem (culture) refers to industrial and agraria culture, work ethos; the second problem (structure) involves capital, market, and technological expertise; whereas the last problem (environment) comprises geographical environment, people's tradition, and internal work culture.In line with those above, The Islamic ethics as a moral foundation in all aspects of life has a significant role in offering ethic guidelines in the Indonesian people's economic order, most of which are Islam (80%). The ethic-normative doctrines in Islam consist of those to take much care of the poor, orphan, equality, ownership in relation to others' rights, fair and just competition, significantly mutual cooperation and so on.